Pengembangan Aplikasi E-Counseling Sebagai Upaya Meningkatkan Pemberian Layanan Bimbingan dan Konseling - Muhammad Nazri Jalil (Indonesian Journal of School Counseling: Theory, Application, and Development, 2021)
This study develops an e-counseling application as an effort to improve the provision of guidance and counseling services at Senior High School 1 Jeneponto. The purpose of this study is to determine: (1) Knowing the field needs of the e-counseling application (2) Knowing the prototype of the e-counseling application as an effort to improve the provision of guidance and counseling services at Senior High School 1 Jeneponto, (3) Knowing the validity of the e-counseling application. as an effort to improve the provision of guidance and counseling services at Senior High School 1 Jeneponto. This study used the Borg and Gall Research and Development (RnD) method but only reached the Second Revision stage. This research was conducted at Senior High School 1 Jeneponto with 6 students as research subjects. The data collection technique used was the Material and Media Expert Validation Sheet to determine the validity of the media and the student response questionnaire. The analysis technique used is descriptive analysis technique. So the results show that the e-counseling application developed has been valid and practically used for the provision of guidance and counseling services at Senior High School 1 Jeneponto.